PROYEK SISTEM ABSENSI FINGERPRINT BERBASIS IoT DENGAN RASPBERRY Pi - Diana Kemala; Eriwandi; Munadi; Dinda Permata; Irvandori (Jurnal Sains Informatika Terapan, 2026)
Attendance recording is an important administrative activity in learning processes at TPQ/TQA Masjid Ihsan Padang. Currently, the attendance system is still conducted manually using attendance books, which often leads to data inaccuracies, loss of records, and inefficiency in reporting. This study aims to develop a student attendance application using fingerprint technology to improve the accuracy, security, and efficiency of attendance management. The research method used is Research and Development (R&D), which includes stages of needs analysis, system design, application development, and system testing. The results of this study indicate that the fingerprint-based attendance application is able to minimize recording errors, prevent attendance fraud, and facilitate faster and more accurate attendance reporting. Therefore, the developed system can be effectively implemented to support administrative activities at TPQ/TQA Masjid Ihsan Padang